EFEKTIFITAS PENGGUNAAN KELAMBU BERINSEKTISIDA (LLINs) TERHADAP KASUS MALARIA (Studi Di Desa Ngreco Kecamatan Tegalombo Kabupaten Pacitan Tahun 2016) - Rizka Ilmawati; Sri Mardoyo; Suroso Bambang Eko Warno (Poltekkes Kemenkes Surabaya, 2017)
ABSTRACTMalaria is a contagious disease that still becomes wide health problem in the world, including Indonesia.In 2014, API of Pacitan was the highest in East Java with 75 patients suffered from malaria. One of the endemicvillage in Pacitan is Ngreco village. Malaria vector control effort undertaken in the village is the use of insecticidetreatedbed nets, as recommended by the World Health Organization (WHO). The use of insecticide-treated netseffectively prevent transmission of malaria when supported with good care to insecticide-treated nets.This study aims to determine the effectiveness of insecticide-treated nets used by Ngreco Villagecommunity as malaria vector control to the decline in malaria cases. This is a quasi-experimental research. Thedata were collected through interview and sampling. The research sample was 29 homes for interviews and 4insecticide-treated nets used by the community for Bio-assay Test.The results of this study shows a decrease in new case of malaria in 2007-2010 from 23 new cases into2 new cases in 2011 to 2015. The results of efficacy test conducted on four samples of net used by thecommunity showed that net with 30 months of use (effectiveness 80%) are no longer effective to be used as avector control of malaria, while net with 12 months of use (effectiveness 80%) is still effective to be used asmalaria vector control.The society should pay more attention on how to laundry the net that it is durable as malaria vectorcontrol. The health center needs to conduct controlling of mosquito nets routinely to find out whether the netsare still effective that replacement or dyeing of the of net can be performed.Keywords: Insecticidal mosquito net, effectiveness, malaria